2014
DOI: 10.5301/jva.5000250
|View full text |Cite
|
Sign up to set email alerts
|

Complex Central Venous Catheter Insertion for Hemodialysis

Abstract: Despite the introduction of payment by results in the UK, there has been no decrease in central venous catheter (CVC) use. In part, this may relate to a requirement to dialyse through a CVC while autogenous access matures. Mortality data have improved in parallel and patients on hemodialysis live longer, which may lead to an increased exposure to CVCs.Exposure to CVCs carries a significant risk of infection and occlusion requiring their repositioning or exchange. The mid to long-term sequelae of CVC use is cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…As presented in these cases and as other authors have previously reported, short-term catheterization of the PLSVC variant with right atrial drainage is safe and effective (7, 17, 18). Powell et al concluded that central venous catheterization via unconventional approaches (collateral veins, occluded veins, translumbar inferior vena cava, transhepatic veins) did not result in poorer complication rates, dialysis flow rates, catheter-related bacteremia, or longevity of access when compared with conventional methods (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in these cases and as other authors have previously reported, short-term catheterization of the PLSVC variant with right atrial drainage is safe and effective (7, 17, 18). Powell et al concluded that central venous catheterization via unconventional approaches (collateral veins, occluded veins, translumbar inferior vena cava, transhepatic veins) did not result in poorer complication rates, dialysis flow rates, catheter-related bacteremia, or longevity of access when compared with conventional methods (1).…”
Section: Discussionmentioning
confidence: 99%
“…Various large-scale initiatives designed to improve these outcomes have resulted in only modest improvement. For example, the UK's payment of surgeons based upon outcomes rather than quantity was associated with only a 16.7% increase in 1-year survival among hemodialysis patients over a 14-year period (63.9% in 1997 vs. 80.6% in 2011), despite concomitant advances in other areas of medicine (1).…”
Section: Introductionmentioning
confidence: 99%
“…28 In exceptional situations, alternative options are translumbar puncture of the inferior vena cava, transhepatic percutaneous access, cannulation of collateral veins and recanalization of obstructed veins. [29][30][31] The access technique is dependent of the vessel chosen. In general, superficial veins (external jugular, cephalic, basilic, and saphenous) are accessed by dissection, whereas deep veins (internal jugular, subclavian, and femoral) are reached by puncture 26,32 ( Figure 2).…”
Section: Techniques For Placement Of Totally Implantable Cathetersmentioning
confidence: 99%
“…One of the long-term sequelae of CVC use is central venous occlusion. [ 1 ] The most commonly sites of placement of dialysis catheters, in order of preference, are right internal jugular vein, left internal jugular vein, external jugular veins, and femoral veins. Rahman and Kuban elaborated unconventional routes of placement of dialysis catheters including placing them through translumbar, transhepatic, and transrenal route.…”
mentioning
confidence: 99%